A qualitative study of patient involvement in medicines management after hospital discharge: an under-recognised source of systems resilience. Issue 7 (16th November 2017) - Fylan, Beth; Armitage, Gerry; Naylor, Deirdre; Blenkinsopp, Alison
Abstract : Introduction: There are risks to the safety of medicines management when patient care is transferred between healthcare organisations, for example, when a patient is discharged from hospital. Using the theoretical concept of resilience in healthcare, this study aimed to better understand the proactive role that patients can play in creating safer, resilient medicines management at a common transition of care. Methods: Qualitative interviews with 60 cardiology patients 6 weeks after their discharge from 2 UK hospitals explored patients' experiences with their discharge medicines. Data were initially subjected to an inductive thematic analysis and a subsequent theory-guided deductive analysis. Results: During interviews 23 patients described medicines management resilience strategies in two main themes: identifying system vulnerabilities; and establishing self-management strategies. Patients could anticipate problems in the system that supplied them with medicines and took specific actions to prevent them. They also identified when errors had occurred both before and after medicines had been supplied and took corrective action to avoid harm. Some reported how they had not foreseen problems or experienced patient safety incidents. Patients recounted how they ensured information about medicines changes was correctly communicated and acted upon, and described their strategies to enhance their own reliability in adherence and resource management. Conclusion: Patients experience the impact of vulnerabilities in the medicines management system across the secondary–primary care transition but many are able to enhance system resilience through developing strategies to reduce the risk of medicines errors occurring. Consequently, there are opportunities—with caveats—to elicit, develop and formalise patients' capabilities which would contribute to safer patient care and more effective medicines management.